Identifying Reservoirs of Infections Caused by Kingella kingae: A Case–Control Study of Oropharyngeal Carriage of K. kingae Among Healthy Adults. Issue 8 (August 2016) - Brändle, Gabriel; Spyropoulou, Vasiliki; Maggio, Albane B.R.; Anderson de la Llana, Rebecca; Cherkaoui, Abdessalam; Renzi, Gesuele; Schrenzel, Jacques; Manzano, Sergio; Ceroni, Dimitri
Abstract : Background: Kingella kingae is currently recognized as a significant pathogen of the pediatric population. Nevertheless, the possibility for adults to serve as a reservoir of healthy carriers has not been studied. Method: We conducted a monocentric transversal study on 228 healthy adults to define the carriage rate. Participants were recruited among the staff of a children's hospital, a population exposed to aerosolized droplets from children. A secondary analysis using a case–control method was conducted to assess risk factors for carriage. Results: We demonstrated an oropharyngeal carriage rate of 2.2% in this population. However, there was a striking similarity in the carriage rate among children younger than 4 years of age and adults living with children of that age group (8.8%). Use of day-care facilities for their own children was also demonstrated as a risk factor for adult carriage. Conclusions: We were able to demonstrate the existence of adult carriage of K. kingae but our results point to transmission from children to adults. Our results do not allow us to conclude that professional exposure in a hospital setting is a risk factor for oropharyngeal carriage.